Method for producing highly crystalline carbon, method for producing precursor thereof, and precursor
By using biomass to prepare semi-graphitide precursor materials for iron oxide nanoparticles and performing high-temperature carbonization and pickling treatment, the problem of traditional high-crystalline carbon material resource depletion is solved, and efficient and sustainable high-crystalline carbon material production is achieved.
Patent Information
- Application Number
- JP2021024718
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-02-18
AI Technical Summary
The production of existing high-crystalline carbon materials depends on resources such as hypereutectic melted iron, natural graphite and graphene that may face resource depletion in the future.
Using biomass as the raw material, semi-graphitides containing iron oxide nanoparticles were prepared as precursor materials through .impregnation and heat treatment, and high-crystalline carbon materials were obtained by high-temperature carbonization and pickling treatment.
The use of sustainable resource biomass to produce high-crystalline carbon materials is achieved, avoiding dependence on traditional resources, and improving the crystal size and plane spacing of the materials.
Smart Images

Figure 0007671488000004 
Figure 0007671488000005 
Figure 0007671488000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing highly crystalline carbon, a method for producing a precursor thereof, and the precursor. [Background technology]
[0002] Conventionally, materials used as anode materials for lithium-ion secondary batteries and catalyst materials for cathodes of fuel cells have been those with relatively large crystallite sizes (Lc, La) and average interplanar spacing (interlayer distance; d 002 In these carbon materials, highly crystalline carbon materials having a relatively small crystallinity are used (see, for example, Patent Document 1 or 2). These highly crystalline carbon materials are produced using, as a raw material, hypereutectic molten pig iron (see, for example, Patent Document 1), natural graphite or kish graphite (see, for example, Patent Document 2), or the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-294101 [Patent Document 2] JP 2000-182617 A Summary of the Invention [Problem to be solved by the invention]
[0004] The highly crystalline carbon materials used in Patent Documents 1 and 2 have the problem that the raw materials, such as hypereutectic molten pig iron, natural graphite, and kish graphite, are exhaustible resources and may be depleted in the future.
[0005] The present invention has been made in light of these problems, and aims to provide a method for producing highly crystalline carbon that can produce highly crystalline carbon using sustainable resources as raw materials, a method for producing a precursor thereof, and the precursor. [Means for solving the problem]
[0006] In order to achieve the above object, the method for producing highly crystalline carbon according to the present invention comprises the steps of: Fe After impregnation, heat treatment at 100℃ to 500℃ in a closed system is performed. The present invention relates to a method for producing a biomass semi-carbonized material, comprising: a semi-carbonized material of biomass; and nanoparticles of iron oxide having a diameter of 20 nm or more, the nanoparticles being dispersed in the semi-carbonized material. The method is characterized by comprising a precursor production step of obtaining a precursor, and a carbonization step of heating the precursor obtained in the precursor production step to 650°C or higher to carbonize it, and then washing it with an acid.
[0007] The method for producing a precursor according to the present invention comprises a precursor production step for the method for producing highly crystalline carbon according to the present invention, and comprises the steps of: Fe After impregnation, heat treatment is performed at 100℃ to 500℃ in a closed system. The biomass semi-carbide and nanoparticles made of iron oxide having a diameter of 20 nm or more are included, and the nanoparticles are dispersed in the semi-carbide. The method is characterized in that a precursor is obtained.
[0008] The method for producing highly crystalline carbon and the method for producing a precursor according to the present invention can use biomass, which is a sustainable resource, as a raw material, and can produce highly crystalline carbon and its precursor, respectively. The highly crystalline carbon produced by the method for producing highly crystalline carbon according to the present invention can be used, for example, as a negative electrode material for lithium ion secondary batteries or a negative electrode material for aluminum ion secondary batteries.
[0009] In the method for producing highly crystalline carbon and the method for producing a precursor according to the present invention, the raw material may be any material containing carbon-containing biomass, and in particular preferably contains plant-based biomass. The plant-based biomass may be any material containing a large amount of plant fiber, such as wood-based materials such as residual wood from trees such as cedars and larch, bark and sawdust, demolished house materials, and pruned wood from roadside trees and garden trees, and herbaceous materials such as waste materials such as rush grass, reeds, and sugar cane.
[0010] The precursor production step and the precursor production method of the highly crystalline carbon production method according to the present invention include: Fe The raw material is immersed in an aqueous solution containing FeIt is preferable to soak the raw material for a period of time that allows the raw material to be sufficiently soaked with Fe, etc., and it is preferable to soak the raw material for a period of time that allows the raw material to be soaked for 12 hours (overnight) or more in order to ensure the soaking. The aqueous solution containing Fe, etc. may be any aqueous solution, and it is preferable to use, for example, an aqueous solution of iron nitrate, which can be easily produced using wood vinegar.
[0011] In the precursor manufacturing step of the method for manufacturing highly crystalline carbon according to the present invention and the method for manufacturing a precursor, the heat treatment may be a heat treatment in a closed system, for example, a hydrothermal treatment or a heat treatment performed in a sealed gas phase. The heat treatment is preferably performed in an inert gas atmosphere such as nitrogen or argon. The heat treatment temperature may be, for example, 200°C or higher, or 300°C or lower, as long as the raw material is semi-carbonized. The heat treatment time may be, for example, 1 to 5 hours, as long as the raw material is semi-carbonized.
[0012] In the method for producing highly crystalline carbon according to the present invention, the carbonization step may be any method capable of carbonizing the precursor. For example, the precursor may be carbonized by firing in a nitrogen atmosphere at 650°C to 1100°C. In addition, in order to further increase the crystallinity, it is preferable to fire at 750°C or higher, and in order to further increase the crystallinity, it is preferable to fire at 900°C or higher. In the carbonization step, highly crystalline carbon can be obtained by simply heating once to the firing temperature, but in order to further increase the crystallinity, it is preferable to set the firing time to 0.5 hours or more, and in order to further increase the crystallinity, it is preferable to set the firing time to 2.5 hours or more. For the acid washing in the carbonization step, it is preferable to use a strong acid solution such as hydrochloric acid or sulfuric acid.
[0013] The precursor according to the present invention comprises a torrefied biomass and Iron oxide with a diameter of 20 nm or more and nanoparticles consisting of the above-mentioned compound, the nanoparticles being dispersed in the semi-carbide.
[0014] The precursor according to the present invention is preferably produced by the method for producing a precursor according to the present invention. The precursor according to the present invention can be further carbonized to obtain highly crystalline carbon. The method for further carbonizing the precursor according to the present invention may be any method that allows carbonization, and may be, for example, the carbonization step of the method for producing highly crystalline carbon according to the present invention.
[0015] In the precursor according to the present invention, the nanoparticles may be made of elemental iron and / or iron oxide. In this case, in order to obtain highly crystalline carbon, the Fe content is preferably about 10 wt% to about 75 wt%, in order to further increase the crystallinity, the Fe content is preferably about 44 wt% to about 75 wt%, and in order to further increase the crystallinity, the Fe content is preferably about 44 wt% to about 58 wt%. In addition, in order to obtain highly crystalline carbon, the nanoparticles are preferably made of Fe3O4 and have a diameter of 20 nm or more, preferably 50 nm or less or 30 nm or less. Effect of the Invention
[0016] According to the present invention, it is possible to provide a method for producing highly crystalline carbon that can produce highly crystalline carbon using sustainable resources as raw materials, a method for producing a precursor thereof, and the precursor. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2A is a cross-sectional view showing a hydrothermal treatment in a method for producing a precursor according to an embodiment of the present invention; FIG. 2B is a cross-sectional view showing a carbonization treatment in a method for producing highly crystalline carbon according to an embodiment of the present invention. [Diagram 2] FIG. 1A is a perspective view showing a step of loading raw materials, etc., into a heat-resistant container, and FIG. 1B is a perspective view showing a step of performing heat treatment on the heat-resistant container, in a method for producing a precursor according to an embodiment of the present invention, in which a precursor is produced by sealing the container in a gas phase and performing heat treatment thereon. [Diagram 3]1(a) shows XRD spectra and (b) shows Raman spectra of precursor samples having different Fe contents produced by the precursor production method according to the embodiment of the present invention shown in FIG. 1(a). [Figure 4] FIG. 1(a) shows transmission electron microscope (TEM) images of precursor samples with different Fe contents, (a) Fe / SD (1:10), (b) Fe / SD (2:10), and (c) Fe / SD (4:10), produced by the precursor production method according to the embodiment of the present invention. [Diagram 5] FIG. 1(a) is a graph showing the results of thermogravimetric analysis (TG) of precursor samples having different Fe contents, (a) Fe / SD (1:10), (b) Fe / SD (2:10), (c) Fe / SD (4:10), and (d) Fe / SD (6:10), produced by the precursor production method according to the embodiment of the present invention shown in FIG. 1(a); and (e) is a graph showing the calculation results of the Fe content of each precursor sample. [Figure 6] 1(a) shows XRD spectra of a precursor sample Fe / SD(4:10) produced by the precursor producing method according to the embodiment of the present invention, and FIG. 2 shows XRD spectra of a precursor sample Fe / SD(4:10)-dry-batch produced by the precursor producing method according to the embodiment of the present invention. [Figure 7] FIG. 1(a) is a graph showing the results of thermogravimetric analysis (TG) of a precursor sample Fe / SD (4:10) produced by the precursor production method according to the embodiment of the present invention shown in FIG. 1(a); FIG. 1(b) is a graph showing the results of thermogravimetric analysis (TG) of a precursor sample Fe / SD (4:10)-dry-batch produced by the precursor production method according to the embodiment of the present invention shown in FIG. 2; and FIG. 1(c) is a graph showing the calculation results of the Fe content of each precursor sample. [Figure 8] FIG. 1(b) shows (a) Raman spectra of carbon samples produced using precursor samples with different Fe contents after acid washing, and (b) Raman spectra of a specified range (Area Average) and two points (Point 1 and Point 2) within the area of carbon sample 4 after acid washing, all of which were produced by a method for producing highly crystalline carbon according to an embodiment of the present invention. [Figure 9]FIG. 1(b) shows XRD spectra of carbon samples (a) before and (b) after acid washing, which were produced using precursor samples with different Fe contents, produced by the method for producing highly crystalline carbon according to an embodiment of the present invention. [Figure 10] FIG. 9(b) is an enlarged view of the XRD spectrum of carbon sample 4 shown in FIG. [Figure 11] FIG. 9(a) is a graph showing the crystallite size (Lc, La) and average interplanar spacing (d002) of each carbon sample calculated from the XRD spectrum shown in FIG. 9(b), and FIG. 9(b) is a perspective view of crystals showing the crystallite size (Lc, La) and average interplanar spacing (d002). [Figure 12] FIG. 1(b) is a graph showing the results of thermogravimetric analysis (TG) of (a) carbon sample 2, (b) carbon sample 3, and (c) carbon sample 4 after acid washing, using precursor samples with different Fe contents produced by the method for producing highly crystalline carbon of an embodiment of the present invention, and (d) a graph showing the calculation results of the weight fraction of highly crystalline carbon in each carbon sample. [Figure 13] FIG. 1(b) shows a TEM image of a carbon sample 4 produced by a method for producing highly crystalline carbon according to an embodiment of the present invention, (a) a TEM image of a crystalline portion of (a), and (c) a TEM image of a non-crystalline portion of (a). [Figure 14] (a) An enlarged TEM image of the highly crystalline portion shown in Figure 13(b), (b) a TEM image of a portion different from (a), (c) a TEM image of a portion different from (a) and (b), and (d) an electron beam diffraction pattern of the highly crystalline portion shown in Figure 13(b). [Figure 15] FIG. 1(b) shows Raman spectra of carbon samples produced by the method for producing highly crystalline carbon according to the embodiment of the present invention using precursor samples having different carbonization temperatures, after washing with acid. [Figure 16] FIG. 1(b) shows XRD spectra of carbon samples produced using precursor samples with different carbonization temperatures, before and after acid washing (a) and after acid washing (b), respectively, produced by the method for producing highly crystalline carbon according to an embodiment of the present invention. [Figure 17]FIG. 16(a) is a graph showing the carbonization yield of carbon samples produced using precursor samples with different carbonization temperatures by the method for producing highly crystalline carbon of an embodiment of the present invention shown in FIG. 1(b); FIG. 16(b) is a graph showing the crystallite size (Lc, La) and average interplanar spacing (d002) of each carbon sample calculated from the XRD spectrum shown in FIG. 16(b). [Figure 18] FIG. 1(b) shows (a) Raman spectra and (b) XRD spectra of carbon samples after acid washing using precursor samples with different carbonization times, which were produced by the method for producing highly crystalline carbon according to an embodiment of the present invention. [Figure 19] FIG. 18(b) is a graph showing the crystallite size (Lc, La) and average interplanar spacing (d002) of each carbon sample calculated from the XRD spectrum shown in FIG. [Figure 20] FIG. 2 shows Raman spectra of a carbon sample 11 obtained by acid washing using a precursor sample produced by the precursor producing method according to the embodiment of the present invention, in a predetermined area (Area Average) and at two points (Point 1 and Point 2) within the area. [Figure 21] 1(b) shows XRD spectra of a carbon sample 4 produced by the method for producing highly crystalline carbon according to an embodiment of the present invention, and a carbon sample 11 using a precursor sample produced by the method for producing a precursor according to an embodiment of the present invention shown in FIG. 2 (a) before and (b) after acid washing. [Figure 22] FIG. 21(b) is a graph showing the crystallite size (Lc, La) and average interplanar spacing (d002) of each carbon sample calculated from the XRD spectrum shown in FIG. [Diagram 23] FIG. 1(a) is a graph showing the results of thermogravimetric analysis (TG) of a carbon sample 4 produced by the method for producing highly crystalline carbon according to an embodiment of the present invention shown in FIG. 1(b); (b) is a graph showing the results of thermogravimetric analysis (TG) of a carbon sample 11 after acid washing using a precursor sample produced by the method for producing a precursor according to an embodiment of the present invention shown in FIG. 2; and (c) is a graph showing the calculation results of the weight fraction of highly crystalline carbon in each carbon sample. [Figure 24]1(a) shows a graph illustrating the relationship between the size of Fe3O4 nanoparticles contained in precursor samples Fe / SD(1:10), Fe / SD(2:10), Fe / SD(4:10), and Fe / SD(6:10) produced by the precursor manufacturing method of an embodiment of the present invention shown in FIG. 1(a), and the precursor sample Fe / SD(4:10)-dry-batch produced by the precursor manufacturing method of an embodiment of the present invention shown in FIG. 2, and the crystallite size Lc of carbon samples 2, 3, 4, 9, and 11 produced from these precursor samples by the highly crystalline carbon manufacturing method of an embodiment of the present invention shown in FIG. 1(b). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiment of the present invention will be described based on examples. In the method for producing the precursor according to the embodiment of the present invention, a raw material containing biomass is impregnated with at least one of Fe, Ni, and Co, and then heat-treated in a closed system at 100° C. to 500° C. This makes it possible to obtain the precursor according to the embodiment of the present invention, which is highly crystalline carbon.
[0019] The raw material may be any material containing carbon-containing biomass, and is particularly preferably plant-based biomass. Plant-based biomass may be any material that contains a large amount of plant fiber, such as woody materials such as tree residues from cedars and larch trees, bark and sawdust, demolished housing materials, and pruned materials from roadside trees and garden trees, and herbaceous materials such as waste materials such as rush grass, reeds, and sugar cane.
[0020] When impregnating the raw material with at least one of Fe, Ni, and Co, it is preferable to soak the raw material in an aqueous solution containing Fe, etc. The soaking time of the raw material may be a time that allows the raw material to be sufficiently impregnated with Fe, etc., and is preferably 12 hours (overnight) or more to ensure impregnation. The aqueous solution containing Fe, etc. may be any type, and is preferably an aqueous solution of iron nitrate, etc., which can be easily produced using wood vinegar, for example.
[0021] The heat treatment may be a heat treatment in a closed system, for example, hydrothermal treatment or heat treatment performed in a sealed gas phase. The heat treatment is preferably performed in an inert gas atmosphere such as nitrogen or argon. The heat treatment temperature may be, for example, 200°C or higher, or 300°C or lower, as long as the raw material is semi-carbonized. The heat treatment time may be, for example, 1 to 5 hours, as long as the raw material is semi-carbonized.
[0022] In the method for producing highly crystalline carbon according to the embodiment of the present invention, the precursor obtained by the method for producing a precursor according to the embodiment of the present invention is heated to 650° C. or higher to be carbonized, and then acid-washed. This results in a carbonized carbon having a relatively large crystallite size (Lc, La) and an average interplanar spacing (interlayer distance; d 002 ) can be obtained.
[0023] When carbonizing the precursor, the precursor may be carbonized by firing at 650°C to 1100°C in a nitrogen atmosphere. In order to further increase the crystallinity, it is preferable to fire at 750°C or higher, and in order to further increase the crystallinity, it is preferable to fire at 900°C or higher. In addition, when carbonizing, highly crystalline carbon can be obtained simply by heating to the firing temperature once, but in order to further increase the crystallinity, it is preferable to set the firing time to 0.5 hours or more, and in order to further increase the crystallinity, it is preferable to set the firing time to 2.5 hours or more. In addition, it is preferable to use a strong acid solution such as hydrochloric acid or sulfuric acid for acid washing.
[0024] The highly crystalline carbon manufacturing method and the precursor manufacturing method according to the embodiment of the present invention can use biomass, which is a sustainable resource, as a raw material, and can respectively manufacture highly crystalline carbon and its precursor. The highly crystalline carbon manufactured by the highly crystalline carbon manufacturing method according to the embodiment of the present invention can be used, for example, as a negative electrode material for lithium ion secondary batteries or a negative electrode material for aluminum ion secondary batteries. EXAMPLES
[0025] First, a precursor sample was produced according to the precursor production method of the embodiment of the present invention. 10 g of larch sawdust with a particle size of 200 μm or less was used as a raw material. In addition, iron nitrate hydrate (Fe(NO3)3·9H2O: Fujifilm Wako Pure Chemical Industries, Ltd., concentration 99.0%) was used to produce a sample with a concentration of 10 to 60 g -Fe A 100 mL aqueous solution of iron nitrate was prepared. As shown in Fig. 1(a), the raw sawdust and 100 mL of the aqueous solution of iron nitrate were placed in a stainless steel autoclave (capacity 500 ml) with the composition shown in Table 1, and left to stand at room temperature for about 12 hours to impregnate the sawdust with Fe. For comparison, 20 g of the raw sawdust and 100 mL of water were placed in a stainless steel autoclave (capacity 500 ml) and left to stand at room temperature for about 12 hours, as shown in Table 1.
[0026] [Table 1]
[0027] After that, N2 purging was performed several times in the autoclave, and then hydrothermal treatment was performed at 250°C for 4 hours as shown in Table 1. In the hydrothermal treatment, the internal pressure was adjusted to about 1 MPa, and the stirring speed was set to 300 rpm. After the hydrothermal treatment, the solid was filtered using a 0.2 μm filter (Merck Millipore's "OMNIPORE (registered trademark)"), washed several times with ultrapure water, and then dried in a thermostatic bath at 105°C for about 12 hours. In this way, the precursor sample shown in Table 1 was obtained. The ultrapure water used was produced using a pure water production device (Yamato Scientific's "WG-220") (the same applies below).
[0028] Next, carbon samples were produced according to the method for producing highly crystalline carbon according to the embodiment of the present invention. As shown in FIG. 1(b), 1.0 g of each precursor sample was charged into an electric tubular furnace, and carbonization was performed at each temperature and time shown in Table 2 while flowing N2 at a flow rate of 200 mL / min, to obtain carbon samples 1 to 9. The heating rate was about 16°C / min. Carbon sample 5 had a carbonization time of 0 hours, and was heated to the carbonization temperature (850°C), after which heating was stopped and the sample was allowed to cool naturally.
[0029] [Table 2]
[0030] In addition, carbon samples 10 to 11 shown in Table 2 were obtained by using precursor samples produced by heat treatment in a sealed gas phase instead of hydrothermal treatment. -Fe The carbon sample was soaked in 100 mL of a 4:10 / L iron nitrate aqueous solution and dried. 1.0 g of the sample was placed in an electric tubular furnace and held at 250°C for 4 hours while flowing N2 at a flow rate of 200 mL / min. This was used as a precursor sample ("Fe / SD(4:10)-dry" in Table 2). The precursor sample was heated in the electric tubular furnace and heat-treated at 850°C for 1 hour to obtain carbon sample 10. Also, as shown in Figure 2(a), 10 g of sawdust was mixed with 100 mL of a 40 g concentration iron nitrate aqueous solution. -Fe The specimen was immersed in 100 mL of a 1 / L aqueous solution of iron nitrate and dried. The specimen was placed in a pressure-resistant vessel (tube reactor, internal volume 10 cm) under a N2 atmosphere. 3 The mixture was placed in a sealed container (manufactured by AKICO Corporation) and then placed in an electric furnace as shown in Fig. 2(b) and heated at 250 °C for 4 hours to obtain the precursor sample (Fe / SD(4:10)-dry-batch in Table 2). 1.0 g of the precursor sample was placed in an electric tubular furnace and heat-treated at 850 °C for 1 hour while flowing N2 at a flow rate of 200 mL / min to obtain carbon sample 11.
[0031] Each precursor sample and each carbon sample were subjected to Raman spectroscopy, crystal structure analysis by X-ray diffraction (XRD), thermogravimetric analysis (TG), and observation by transmission electron microscope (TEM). In the Raman spectroscopy, a diffraction grating of 600 gr / mm and a central wave number of 2000 cm were used. -1 The measurements were performed with an exposure time of 10 s and an accumulation count of 10. For X-ray diffraction, a horizontal sample type multipurpose X-ray diffractometer (RIGAKU Corporation) was used, with a measurement range of 10 to 60 deg, a scanning speed of 2.0 deg / min, a tube voltage of 40 kV, and a tube current of 40 mA.
[0032] For the thermogravimetric analysis, a TG / DTA6200 (EXSTAR6000 series, manufactured by Seiko Instruments Inc.) was used. For each precursor sample, the temperature was raised to 900°C at a rate of 10°C / min with N2 gas, then the gas was switched to air and held for about 15 minutes. For each carbon sample, the temperature was raised from room temperature to 450°C (10°C / min) with air flowing at 200 ml / min, held for 10 minutes, then raised again to 600°C (10°C / min), and finally raised to 700°C at 50°C / min. For the transmission electron microscope (TEM) observation, a HT-7500 (manufactured by Hitachi, Ltd.) was used to observe the morphology and structure of the samples. In addition, an energy dispersive X-ray spectrometry (TEM-EDS) was performed using a JEM-2100F (manufactured by JEOL).
[0033] [Precursor sample] X-ray diffraction measurements and Raman spectroscopy were performed on the precursor samples Fe / SD (1:10), Fe / SD (2:10), Fe / SD (4:10), and Fe / SD (6:10) shown in Table 1. The XRD and Raman spectra of each precursor sample are shown in Figure 3(a) and (b), respectively. As shown in Figure 3(a), peaks derived from iron oxide (Fe3O4) were observed in each precursor sample, and it was confirmed that these peaks became larger as the amount of Fe added increased. Furthermore, no peaks derived from cellulose were observed in any of the precursor samples. This is thought to be because the crystalline structure of cellulose was lost due to hydrothermal carbonization.
[0034] As shown in Fig. 3(b), each precursor sample showed a D band (1350 cm -1 near 1580 cm -1A broad peak was observed around 1000 nm, confirming that the carbon structure had developed slightly and that the material had become semi-carbonized. In addition, in the precursor samples Fe / SD (2:10), Fe / SD (4:10), and Fe / SD (6:10), it was confirmed that the D band developed slightly as the amount of Fe added increased, which is considered to indicate that carbonization had progressed. Note that the precursor sample Fe / SD (0:20), which had no added Fe, showed almost no carbonization and the Raman spectrum could not be measured.
[0035] Figure 4 shows the TEM observation results for the precursor samples Fe / SD (1:10), Fe / SD (2:10), and Fe / SD (4:10). As shown in Figure 4, the black shaded areas are Fe3O4, and it was confirmed that Fe3O4 nanoparticles were uniformly dispersed within the structure of the precursor sample. It was also confirmed that the number of Fe3O4 particles increases and the Fe3O4 particles tend to become larger as the amount of Fe added increases. In the precursor sample Fe / SD (4:10), Fe3O4 makes up the majority, confirming the presence of a large amount of Fe3O4 in the precursor sample.
[0036] Thermogravimetric analysis (TG) was performed on the precursor samples Fe / SD (1:10), Fe / SD (2:10), Fe / SD (4:10), and Fe / SD (6:10). The results are shown in Figure 5(a)-(d), respectively. In addition, the Fe content of each precursor sample was calculated assuming that all remaining Fe was Fe2O3, and the results are shown in Figure 5(e). As shown in Figure 5(a)-(d), a large weight loss was confirmed at around 600°C for each precursor sample. This is thought to be because carbon becomes CO and vaporizes when FeO is reduced to Fe or Fe3C. In addition, as shown in Figure 5(e), it was confirmed that the Fe content of each precursor sample increased with an increase in the amount of Fe added. From this result, it is thought that the amount of Fe doped in the precursor sample can be controlled.
[0037] X-ray diffraction measurements were performed on the precursor sample Fe / SD(4:10) and the precursor sample Fe / SD(4:10)-dry-batch used for carbon sample 11. The XRD spectrum of each precursor sample is shown in Figure 6. As shown in Figure 6, peaks derived from iron oxide (Fe3O4) were observed in each precursor sample, but in the precursor sample Fe / SD(4:10) that underwent hydrothermal treatment, the peaks were of the (Fd-3m) type, while in the precursor sample Fe / SD(4:10)-dry-batch that underwent heat treatment in a sealed gas phase, there were more (R-3m) type peaks. It was confirmed that iron oxides with different structures were produced due to the difference in heat treatment.
[0038] Thermogravimetric analysis (TG) was performed on the precursor sample Fe / SD(4:10) and the precursor sample Fe / SD(4:10)-dry-batch used for carbon sample 11. The results are shown in Figures 7(a) and (b), respectively. In addition, the Fe content of each precursor sample was calculated assuming that all remaining Fe was Fe2O3, and is shown in Figure 7(c). The Fe content of the precursor sample Fe / SD(4:10) is the same as that shown in Figure 5(e). As shown in Figures 7(a) and (b), a large peak was confirmed at around 400 min in the precursor sample Fe / SD(4:10)-dry-batch, whereas almost no peak was observed at around 400 min in the precursor sample Fe / SD(4:10). This peak is a weight loss peak caused by the decomposition of cellulose and hemicellulose, and it is thought that it did not appear in the precursor sample Fe / SD(4:10) because cellulose and other substances were decomposed and converted into monomers, which were then polymerized. Furthermore, as shown in Figure 7(c), it was confirmed that the precursor sample that underwent hydrothermal treatment had a higher Fe content than the precursor sample that underwent heat treatment in a sealed gas phase.
[0039] [Fe addition amount] The effect of the amount of Fe added to the sawdust raw material was investigated for carbon samples. Carbon samples 2, 3, 4, and 9, which had different amounts of Fe added and were carbonized at 850°C for 1 hour, were subjected to acid washing with HCl and then Raman spectroscopy analysis. The results are shown in Figure 8(a). As shown in Figure 8(a), carbon samples 2, 3, and 4 showed a G band (1580 cm -1 near 1350 cm -1 near 2700 cm), 2D band ( -1 In carbon sample 9, peaks were observed in the G band and D band, but no peak was observed in the 2D band. In addition, compared to carbon samples 2, 3, and 9, carbon sample 4 had a relatively low D band peak due to structural defects, and high and sharp G band and 2D band peaks, confirming a higher degree of carbonization.
[0040] FIG. 8(b) shows the results of Raman spectroscopy performed on carbon sample 4 after acid washing at two points within a specified range (measurement range in FIG. 8(a)). It was confirmed that the D-band peak was higher than the G-band peak at the point indicated by the black shadow (Point 1) in carbon sample 4. Therefore, it is considered that carbonization has not progressed at this point. In contrast, it was confirmed that the D-band peak was relatively low at the point not indicated by the black shadow (Point 2), and the G-band was high and sharp, and the 2D-band was also sharp. Therefore, it is considered that highly crystalline carbon exists at this point. From this result, it can be said that carbon sample 4 has a highly crystalline portion and a relatively low crystalline portion, and that the crystallinity varies depending on the location.
[0041] X-ray diffraction measurements were performed on carbon samples 1, 2, 3, 4, and 9, which were carbonized at 850°C for 1 hour with different amounts of Fe added. Figure 9(a) shows the XRD spectra of carbon samples 2, 3, 4, and 9 before acid washing with HCl, and Figure 9(b) shows the XRD spectra of carbon samples 1, 2, 3, 4, and 9 after acid washing with HCl. As shown in Figure 9(a), in carbon samples 2, 3, and 4 before acid washing, a peak derived from α-Fe (peak near 45 degrees) or a peak derived from Fe3C (cementite) was confirmed. In carbon sample 2, which has a small amount of Fe added, almost no α-Fe peak was observed, and a peak of Fe3C was observed, but as the amount of Fe added increased, the α-Fe peak became larger, and in carbon sample 4, almost only α-Fe was observed, and no Fe3C peak was observed. In carbon sample 9, almost no α-Fe peak or Fe3C peak was observed, and a peak of FeO was confirmed.
[0042] As shown in Fig. 9(b), in carbon sample 1, which does not contain Fe, broad peaks were observed around 26 degrees and 44 degrees. This pattern is similar to the XRD pattern of hard carbon, etc., and it can be said that the carbonized sample is carbonized. In addition, in carbon samples 2, 3, and 4, a peak (peak around 26 degrees) originating from the (002) plane of graphite was observed, and it was confirmed that the peak became larger and sharper as the amount of Fe added increased. In addition, comparing Fig. 9(a) and (b), in carbon samples 2, 3, and 4, the α-Fe peak disappeared after acid washing, and it was confirmed that α-Fe was removed by HCl. In carbon samples 2 and 3, Fe3C peaks were observed even after acid washing, and Fe3C could not be completely removed even by acid washing. In carbon sample 9, a few peaks originating from the (002) plane of graphite were observed, but almost no Fe3C peaks were observed. This is thought to be because iron oxide remains in carbon sample 9. Since the (002) plane was developed in the Fe-containing carbon samples 2, 3, 4, and 9, it is believed that the addition of Fe caused catalytic graphitization, leading to the formation of highly crystalline carbon.
[0043] When highly crystalline carbon is used as a negative electrode material for lithium-ion secondary batteries, the presence of Fe3C reduces performance. The results in Figure 9 show that since Fe3C cannot be completely removed by acid washing, it is necessary to consider the composition of the precursor and the heat treatment conditions in order to remove Fe3C.
[0044] An enlarged XRD spectrum of carbon sample 4 after acid washing is shown in Figure 10. As shown in Figure 10, carbon sample 4 showed a peak derived from the (100) plane of graphene (peak near 42 degrees) and a peak derived from the (004) plane (peak near 54 degrees), which were not observed in other carbon samples.
[0045] From the XRD spectrum, it can be seen that in the precursor sample Fe / SD (4:10) after hydrothermal carbonization, Fe was present in the form of Fe3O4 (see Figure 3(a)), but the Fe was reduced to α-Fe by the carbonization process (see Figure 9(a)), and by further acid washing, only highly crystalline carbon was confirmed (see Figure 9(b) and Figure 10).
[0046] From the XRD spectra shown in Fig. 9(b), the crystallite size (Lc, La) and average interplanar spacing (d 002 The crystallite size (Lc, La) and the average interplanar spacing (d 002 ) are the sizes shown in Figure 11(b). Note that in carbon samples 2 and 3, the presence of Fe3C made it difficult to analyze the peak of the (100) plane, so the crystallite size La was determined only for carbon sample 4. As shown in Figure 11(a), it was confirmed that increasing the amount of Fe added increases Lc and develops a layered structure. It was also confirmed that La in carbon sample 4 grows significantly. The average interplanar spacing d 002It was confirmed that the amount of Fe added decreases with increasing the amount of Fe added. Generally, as the crystal structure develops, the interplanar spacing narrows and approaches 0.336 nm. Therefore, it can be said that the crystallinity of the carbide develops with increasing the amount of Fe added. In particular, for carbon samples 4 and 9, the graphite CIP material (Lc is about 30 to 70 nm, La is about 30 to 60 nm, d 002 It was confirmed that the crystallinity was equivalent to that of the SiO2 nanoparticles (approximately 0.337 nm).
[0047] Thermogravimetric analysis (TG) was performed on carbon samples 2, 3, and 4 after acid washing. The results are shown in Figure 12(a) to (c), respectively. As shown in Figure 12(a) to (c), large weight losses were confirmed around 200 to 400 °C and 500 to 600 °C. Since graphite gasifies at 500 °C or higher in an air atmosphere, the weight loss around 200 to 400 °C is attributed to the gasification of the carbon in the non-crystalline portion, and the weight loss around 500 to 600 °C is attributed to the gasification of the highly crystalline carbon. In addition, when comparing DTG, it was confirmed that the weight loss due to the highly crystalline carbon shifted to the high temperature side (right side) as the Fe content increased. Since the higher the crystallinity of carbon, the higher the gasification temperature, it can be said that the crystallinity increases as the Fe content increases.
[0048] From the results in Figures 12(a)-(c), the weight fraction of highly crystalline carbon was calculated using equation (1). The weight reduction from the temperature of approximately 450°C, where the DTG peak is at its minimum, to 700°C was considered to be solely due to the gasification of highly crystalline carbon, and the weight ratio of highly crystalline carbon to all organic matter with the Fe content subtracted was calculated. The results are shown in Figure 12(d). Note that in equation (1), all remaining Fe is considered to be Fe2O3, and 0.669 in equation (1) is the weight ratio of iron in Fe2O3.
[0049]
number
[0050] As shown in Figure 12(d), it was confirmed that the proportion of highly crystalline carbon increases when the Fe content is increased. This means that a higher Fe content reduces the amorphous proportion and produces crystalline carbon with higher purity. This is thought to be because the amorphous portion becomes easier to gasify as the catalytic gasification of Fe progresses at the same time as the high crystallization progresses.
[0051] The results of observation of carbon sample 4 after acid washing using a transmission electron microscope (TEM) are shown in Figure 13. As shown in Figure 13(a), it was confirmed that there were highly crystalline and amorphous parts. As shown in Figure 13(b), it was confirmed that the highly crystalline parts were onion-shaped and had a structure similar to graphite shell chains (GSCs). As shown in Figure 13(c), it was confirmed that the amorphous parts were a mixture of non-graphene-like non-crystals and relatively small graphite shell chains.
[0052] Enlarged TEM images of the highly crystalline portion shown in FIG. 13(b) are shown in FIG. 14(a)-(c). The electron beam diffraction pattern of the highly crystalline portion is shown in FIG. 14(d). As shown in FIG. 14(a)-(c), the highly crystalline portion shows that the graphene sheets are stacked in parallel, and that a large crystal structure of 20 nm or more has developed. As shown in FIG. 14(d), the electron beam diffraction pattern shows that the diffraction lines of the (002) and (100) planes appear in a ring shape, confirming that the portion has a polycrystalline structure. In addition, in the portion with strong diffraction and large crystal size, the diffraction lines of the (101) and (110) planes were also confirmed.
[0053] From the above results, when producing a precursor, by setting the weight ratio of Fe to the raw material consisting of woody biomass to Fe:raw material = 0.5 to 7:10, the Fe content in the precursor becomes about 10 wt% to about 75 wt%, and it can be said that highly crystalline carbon can be obtained. Also, by setting the Fe:raw material = 3 to 7:10, the Fe content in the precursor becomes about 44 wt% to about 75 wt%, and it can be said that carbon with higher crystallinity can be obtained and Fe3C can also be removed. Also, by setting the Fe:raw material = 3 to 5:10, the Fe content in the precursor becomes about 44 wt% to about 58 wt%, and it can be said that carbon with even higher crystallinity can be obtained.
[0054] [About carbonization temperature] Carbon samples 4, 7, and 8, which had the same amount of Fe added and were carbonized at different carbonization temperatures for 1 hour, were washed with HCl and then subjected to Raman spectroscopy. The results are shown in Figure 15. The Raman spectrum of carbon sample 4 is the same as that shown in Figure 8. As shown in Figure 15, peaks were confirmed in the G band, D band, and 2D band for all of carbon samples 4, 7, and 8. However, it was confirmed that the G band of carbon sample 7 was somewhat broader than those of carbon samples 4 and 8, and the development of the 2D band was also slight. From this, it is considered that the development and stacking of graphene sheets did not progress very much at the carbonization temperature of 700°C.
[0055] X-ray diffraction measurements were performed on carbon samples 4, 7, and 8 before and after acid washing with HCl. The XRD spectrum before acid washing is shown in FIG. 16(a), and the XRD spectrum after acid washing is shown in FIG. 16(b). The XRD spectrum of carbon sample 4 is the same as that shown in FIG. 9. As shown in FIG. 16(a), strong peaks derived from α-Fe were observed in carbon samples 4, 7, and 8 before acid washing, but peaks derived from Fe3C were hardly observed. In addition, as shown in FIG. 16(b), peaks derived from the (002) plane of graphite were observed in carbon samples 4, 7, and 8. Although the peaks were weak in carbon samples 4 and 7, the peaks of the (100) plane (peak near 42 degrees) and the peaks of the (004) plane (peak near 54 degrees) were also confirmed in carbon samples 4, 7, and 8.
[0056] The yield of carbonized products of carbon samples 4, 7, and 8 relative to the amount of raw sawdust was calculated and is shown in Figure 17(a). In addition, the crystallite size (Lc, La) and average interplanar spacing (d 002 ) was calculated. The results are shown in Figure 17(b). The results for carbon sample 4 are the same as those shown in Figure 11(a). As shown in Figure 17(a), it was confirmed that carbon sample 4 had the highest yield. Also, as shown in Figure 17(b), it was confirmed that the higher the carbonization temperature, the larger the crystal size and the smaller the average interplanar spacing. From this, it can be said that crystallization is more likely to proceed when the carbonization temperature is higher.
[0057] From the above results, it can be said that highly crystalline carbon can be obtained by setting the temperature during carbonization of the precursor to 650° C. to 1100° C. In addition, it can be said that carbon with higher crystallinity can be obtained by setting the temperature to 750° C. to 1100° C., and carbon with even higher crystallinity can be obtained by setting the temperature to 900° C. to 1100° C.
[0058] [About carbonization time] Carbon samples 4, 5, and 6, which had the same amount of Fe added and were carbonized at 850°C for different times, were washed with HCl and then subjected to Raman spectroscopy. The results are shown in Figure 18(a). The Raman spectrum of carbon sample 4 is the same as that shown in Figure 8. As shown in Figure 18(a), it was confirmed that the G band peak of carbon sample 5 is somewhat broader and the 2D band peak is somewhat lower than those of carbon samples 4 and 6. From this, it is considered that the development and stacking of graphene sheets is not very advanced in carbon sample 5. In addition, although not shown, it was confirmed that the difference in crystallinity between measurement points is small in carbon sample 6. From this, it can be said that a uniform carbon structure is approached by increasing the time of carbonization.
[0059] X-ray diffraction measurements were performed on carbon samples 4, 5, and 6 after acid washing with HCl. The results are shown in Figure 18(b). The XRD spectrum of carbon sample 4 is the same as that shown in Figure 9(b). As shown in Figure 18(b), peaks originating from the (002) and (004) planes of graphite were confirmed in all of carbon samples 4, 5, and 6. This suggests that graphitization has progressed to a certain extent when the temperature reaches 850°C during the carbonization process. In addition, peaks thought to be originating from iron oxide (Fe3O4) were observed in carbon sample 6 at around 30°C, 36°C, and 41°C.
[0060] From the XRD spectrum shown in Fig. 18(b), the crystallite size (Lc, La) and the average interplanar spacing (d 002 ) was calculated. The results are shown in Figure 19. The results for carbon sample 4 are the same as those shown in Figure 11(a). As shown in Figure 19, it was confirmed that the longer the carbonization time, the larger the crystal size. From this, it can be said that the reaction progresses and the crystallinity increases with the carbonization time.
[0061] From the above results, it can be said that highly crystalline carbon can be obtained by once heating the precursor to the carbonization temperature when carbonizing it. In addition, it can be said that carbon with higher crystallinity can be obtained by setting the carbonization time to 0.5 hours or more, and carbon with even higher crystallinity can be obtained by setting the carbonization time to 2.5 hours or more.
[0062] [Carbonization method] Carbon samples 4 and 11, which had the same amount of Fe added, were carbonized at 850°C for 1 hour using different precursor sample manufacturing methods. After acid washing with HCl, Raman spectroscopy was performed. As in Figure 8(b), Raman spectroscopy was performed at two points: a specified range, a point with black shadow (Point 1), and a point without black shadow (Point 2). The Raman spectrum of carbon sample 4 is shown in Figure 8(b), and the Raman spectrum of carbon sample 11 is shown in Figure 20. It was confirmed that the G band and 2D band were developed in the specified range for both carbon samples, and the D band had a smaller intensity than the G band. Compared to carbon sample 11, carbon sample 4 has a sharper 2D, which is considered to have a more developed layered structure. In addition, differences in the spectra at each measurement point were observed for both carbon samples, which means that there are differences in crystallinity depending on the location.
[0063] X-ray diffraction measurements were performed on carbon samples 4 and 11 before and after acid washing. The XRD spectrum before acid washing is shown in FIG. 21(a), and the XRD spectrum after acid washing is shown in FIG. 21(b). The XRD spectrum of carbon sample 4 is the same as that shown in FIG. 9(a) and (b). As shown in FIG. 21(a), peaks derived from α-Fe were confirmed in carbon samples 4 and 11 before acid washing. In addition, a peak derived from Fe3C was also confirmed in carbon sample 11. As shown in FIG. 21(b), peaks derived from the (002) plane of graphite were confirmed in both carbon samples 4 and 11 after acid washing. From this, it was confirmed that highly crystalline carbon can be developed even if the precursor sample is produced by heat treatment in a sealed gas phase instead of hydrothermal treatment. In carbon sample 11, a peak derived from Fe3C was confirmed even after acid washing.
[0064] From the XRD spectrum shown in FIG. 21(b), the crystallite size (Lc, La) and the average interplanar spacing (d 002 ) was calculated. The results are shown in FIG. 22. The results for carbon sample 4 are the same as those shown in FIG. 11(a). As shown in FIG. 22, it was confirmed that the crystal size of carbon sample 4 was larger than that of carbon sample 11, and the average interplanar spacing of carbon sample 11 was smaller than that of carbon sample 4. From this, it can be said that if hydrothermal treatment is performed when producing a precursor sample, large-sized highly crystalline carbon is produced, and if heat treatment is performed in a sealed gas phase when producing a precursor sample, relatively uniformly small highly crystalline carbon is produced.
[0065] Thermogravimetric analysis (TG) was performed on carbon samples 4 and 11 after acid washing. The results are shown in Figures 23(a) and 23(b), respectively. The weight fraction of highly crystalline carbon was calculated using equation (1), and the result is shown in Figure 23(c). As shown in Figure 23(a), two DTG peaks were confirmed in carbon sample 4, but as shown in Figure 23(b), the peak at 500°C or higher in carbon sample 11 was broad, and it was confirmed that the weight continued to decrease in the high temperature range. From this result, it can be said that carbon sample 11 has a carbon structure with non-uniform crystallinity, and a wide range of carbon exists uniformly, from amorphous carbon to highly crystalline carbon that does not vaporize until around 600°C. Also, as shown in Figure 23(c), it was confirmed that the weight fraction of highly crystalline carbon is almost the same for both carbon samples 4 and 11.
[0066] From the above results, it can be said that highly crystalline carbon can be obtained whether the precursor is produced by hydrothermal treatment or by heat treatment in a sealed gas phase.
[0067] FIG. 24 shows the relationship between the size of the Fe3O4 nanoparticles contained in the precursor samples Fe / SD(1:10), Fe / SD(2:10), Fe / SD(4:10), Fe / SD(6:10), and Fe / SD(4:10)-dry-batch and the crystallite size Lc of carbon samples 2, 3, 4, 9, and 11 produced from those precursor samples. The size of the Fe3O4 nanoparticles was determined from the XRD analysis results of each precursor sample. The crystallite size Lc of each carbon sample is the same as that shown in FIG. 11(a) and FIG. 22. As shown in FIG. 24, it was confirmed that by increasing the amount of Fe charged to the raw material, the size (diameter) of the Fe3O4 nanoparticles contained in the precursor sample increases and the crystallinity improves. For example, when the size of the Fe3O4 nanoparticles contained in the precursor sample is 20 nm or more, highly crystalline carbon with a crystallite size Lc of about 30 nm or more can be obtained.
Claims
1. a precursor production process in which a raw material containing biomass is impregnated with Fe, and then heat-treated at 100°C to 500°C in a closed system to obtain a precursor containing semi-carbide of the biomass and nanoparticles made of iron oxide having a diameter of 20 nm or more, the nanoparticles being dispersed in the semi-carbide; a carbonization step in which the precursor obtained in the precursor production step is carbonized by heating to 650° C. or higher, and then subjected to acid washing; A method for producing highly crystalline carbon, comprising the steps of:
2. 2. The method for producing highly crystalline carbon according to claim 1, wherein the raw material includes plant biomass.
3. 3. The method for producing highly crystalline carbon according to claim 1, wherein the precursor production step comprises immersing the raw material in an aqueous solution containing Fe, thereby impregnating the raw material with Fe.
4. 4. The method for producing highly crystalline carbon according to claim 1, wherein the heat treatment in the precursor production step is a hydrothermal treatment.
5. The method for producing highly crystalline carbon according to any one of claims 1 to 4, characterized in that the precursor production process comprises impregnating the raw material with Fe so that the weight ratio of the biomass to the Fe is 10:0.5 to 7.
6. 6. The method for producing highly crystalline carbon according to claim 1, wherein the carbonization step carbonizes the precursor by baking the precursor at 650° C. to 1100° C. in a nitrogen atmosphere.
7. A method for producing a precursor, comprising the steps of: impregnating a raw material containing biomass with Fe, and then heat-treating the raw material at 100°C to 500°C in a closed system to obtain a precursor containing semi-carbide of the biomass and nanoparticles made of iron oxide having a diameter of 20 nm or more, the nanoparticles being dispersed in the semi-carbide.
8. The method for producing a precursor according to claim 7, wherein the raw material includes a plant-based biomass.
9. A method for producing a precursor according to claim 7 or 8, characterized in that the raw material is impregnated with Fe by immersing the raw material in an aqueous solution containing Fe.
10. 10. The method for producing a precursor according to claim 7, wherein the heat treatment is a hydrothermal treatment.
11. The method for producing a precursor according to any one of claims 7 to 10, wherein the raw material is impregnated with the Fe so that the weight ratio of the biomass and the Fe is 10:0.5-7.
12. Semi-carbonized biomass; and nanoparticles made of iron oxide having a diameter of 20 nm or more; The nanoparticles are dispersed in the semi-carbide. Characterized precursors.
13. 13. The precursor of claim 12, wherein the nanoparticles have an Fe content of about 10 wt % to about 75 wt %.
14. The nanoparticles are Fe 3 O 4 14. The precursor according to claim 12 or 13, characterized in that it consists of:
Citation Information
Patent Citations
Graphite for lithium secondary battery cathode and manufacture of same
JP1998294101A
Carbon material for lithium secondary battery electrode and its manufacture, and lithium secondary battery
JP2000182617A
Magnetic activated carbon and methods for preparing and regenerating such materials
JP2015530236A
Graphite production from biomass
JP2018511553A